About the current Issue - Paetau, Michael (Journal of Sociocybernetics, 2013)
The current edition places the discussion of “Sustainable Development” into the center of interest. The first two articles attend the social dimension of the tridimensional approach of Sustainabiliy (ecological, economic and social dimension). Luciano Gallón starts with his article “Poverty and Artificial Sustainability. A research on the Structure and Dynamics of South America” where he shows the process of building a theoretical and practical framework for modelling South America using the approach of Systems Dynamics. Based on this concept he wants to explore questions such as: Is it possible to reduce poverty following a sustainable path? What is the kind of steady state behind the sustainability ideas? In what sense is it possible to talk of artificial sustainability? What relationship can be found between the scales of space and time of the human perspective and of the sustainability and the dynamics of the new social equilibriums? How such exploration enriches the understanding of social systems and human behavior? What contributions can be offered from such analysis and synthesis to contribute to sustainability? How can the structure and dynamics of South America helps to answer those questions?The social dimension of Sustainable Development is also focussed in the following contribution.  Darío Menanteau-Horta analyses in his article “Globalization and Distorted Development: In Search of a System Perspective for Sustainability” the topic of Sustainable Development within the controversy between those who promise prosperity and opportunities in an expanded and international world market and those who claim that globalization, as it has been carried on today, is a negative force for peace, equity, and social development.In his Short Communication to this topic Nils O. Larsson suggests a methodology to find the most important decisions within a specific area of discussion. Focussing on the important decisions and in which settings they are taken gives an increased possibility of solving the problems in question. In this actual subject the analysis should cover decisions on all levels i.e. individual, informal and formal groupings of people, nations, group of nations as well as decisions on the global level.In continuation of his “Introduction into Sociocybernetics”, published in the last edition of JoS, Roberto Gustavo Mancilla presents now the second part focussing the relationship between power, culture and institutions. The third part in which the question of rationality and language will be discussed follows in the next issue of the Journal of Sociocybernetics.Michael Paetau (Editor)